The legal Woes of appraising professional performance - Rozovsky, Lorne; Rozovsky, Fay (Operating Room Nurses Association of Canada Journal, 1987)
One of the more important aspects of quality assurance is the so—called “Professional Performance Appraisal.” Designed to assess the quality of care provided by a nurse/caregiver, the process is seemingly a neutral, objective exercise.